The Use of Tunable Encapsulation for Long-Term Fouling Control - Emily Ralston; Samantha Pringle (Journal of Marine Science and Engineering, 2023)
Biofouling is a universal problem in the marine environment. Static structures and niche areas on ships, such as propellers, are not protected sufficiently by antifouling coatings. Encapsulation has previously been used as a fouling mitigation technique via application of an impermeable wrap or bag to a fouled hull or structure when it arrives in port or on station. This experiment investigated the use of a novel semipermeable encapsulation to proactively protect propeller mimics from biofouling. Sleeves were installed over propeller mimic panels and deployed in an active, multiuse port for 20 months. The sleeves completely prevented macrofouling on the panels for up to 13 months and maintained surfaces below 5% cover for the entire experimental period. This shows improvement over traditional antifouling without negative impacts on water quality like dissolved oxygen, pH, etc.